Story, myth, and celebration in old French narrative poetry : 1050-1200 - Uitti, Karl D. (Princeton legacy library., 1973)
Twelfth-century France has been described as the key to many of the most important developments of medieval civilization. Nowhere is this description more accurate than in the domain of poetic invention. The years 1050 to 1200 witnessed the development of a brilliant body of vernacular narrative that not only expressed the complexity of its own time but also bequeathed to posterity a wide gamut of creative possibilities. Although much has been written about the works of this period, Karl Uitti offers the first critically orientated overview of this poetry as poetry. In the sections devoted t.